Pengembangan Model Tata Kelola Layanan Bimbingan dan Konseling Online Berbasis Website - Panggih Wahyu Nugroho; Dwi Ulfa Nurdahlia (Universitas Islam Negeri Kiai Ageng Muhammad Besari Ponorogo (previously known as IAIN Ponorogo), 2024)
Various changes in the field of guidance and counseling are responses to the emergence of various problems in society. These shifts have triggered the rise of more complex issues, such as stress caused by life pressures, relationship problems, and increasingly prevalent mental health challenges. Product development is carried out to facilitate the implementation of counseling services, addressing the various issues faced by students, including personal-social, academic, and career problems. Online counseling development integrates various platforms already familiar to users, such as email, chat, and video calls, into a single website. This product offers advantages over previous products. One of its key features is the website's development, which is designed with simple and efficient management. The user-friendly design enables users to register easily without any difficulties. Additionally, the efficient registration process enhances user comfort and satisfaction. With more practical features, the product is expected to reach a broader range of users. The method applied is R&D, or Research and Development, which will ultimately result in a specific product. The development method used is the 4D development model, consisting of four stages: Define, Design, Development, and Dissemination. Based on research on the management of web-based online guidance and counseling services, it can be concluded that the management of web-based online guidance and counseling services can be implemented by preparing the website layout, collecting client data via the web, scheduling counseling services, and executing counseling sessions.